Keanekaragaman Jenis Burung di Berbagai Kawasan Kampus Pulau Sumatra - Andika Jefriawan; Mesita Saura; Khairul Abdi; Frisca Rohmaulina Limbong; Afifah Ruwaidah; Muhammad Ichsan; Aida Fithri; Widya Sari (Jurnal Bioleuser, 2024)
Sumatra Island is one of the westernmost islands of Indonesia, which has various types of birds. Therefore, this research was carried out to analyze the diversity of bird species in various areas of the Sumatra Island campus. This research was conducted using a literature review method with Google Scholar. The results of the research show that there are 10 campus areas on Sumatra Island which are recorded as having a diversity of bird species, namely Syiah Kuala University had 10 bird species, Andalas University had 24 bird species, Lampung University had 20 bird species, Bangka Belitung University had 20 bird species, Raden University Intan Lampung had 24 bird species, Bengkulu University had 12 bird species, UIN Ar-Raniry had 15 bird species, Sumatra Institute of Technology had 19 bird species, Riau University had 48 bird species and Padang University had 21 bird species.